Evaluation of extenders for the cooling of rabbit semen (Oryctolagus cuniculus) - Suárez A., Camila (2020)
The aim of this research was to evaluate the use of different extenders for cooling of rabbit semen and its effect on sperm quality. Thirty semen samples from 10 sexually mature rabbits (Oryctolagus cuniculus) were used. Each sample was diluted separately in a 1:10 ratio in four extenders, composed of skim milk and sugars (T1); dextrose, sodium citrate, and potassium acetate (T2); sodium caseinates, phosphates and sugars (T3); and tris-citric acid and egg yolk (T4). The semen was kept at 16 °C for 72 hours. At the time of dilution and every 24 hours, total motility (MT), progressive motility (MP) and sperm kinetics were evaluated with the Sperm Class Analyzer® system, and vitality and morphology were evaluated by the eosin-nigrosin staining. Statistical analysis was performed using mixed models and the comparison of means by the Duncan test. At the time of dilution (0 h), a lower MT for T2 and T4 was observed (p<0.05). This same effect at 24 h of cooling was observed, while at 48 h the MT was lower for T2, compared to T1, T3 and T4 (p <0.05). The MP was equally higher for T1 and T3 at 0, 24 and 48 h (p<0.05). A decrease in normal morphology at 72 h for T4 was found (p<0.05). Greater preservation of the viability over time for T1 and T3 was observed (p<0.05). It is concluded that the extenders composed by skim milk or caseinates, and sugars, protect more efficiently the rabbit semen preserved by refrigeration.